1998
DOI: 10.1073/pnas.95.5.2630
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalgesia in mice with a targeted deletion of the tachykinin 1 gene

Abstract: The tachykinin neuropeptides, substance P and substance K, are produced in nociceptive primary sensory neurons and in many brain regions involved in pain signaling. However, the precise role and importance of these neuropeptides in pain responses has been debated. We now show that mice that cannot produce these peptides display no significant pain responses following formalin injection and have an increased pain threshold in the hotplate test. On the other hand, the mutant mice react normally in the tail f lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 58 publications
7
103
2
Order By: Relevance
“…These data are also consistent with previous reports of behavioral deficits in animals lacking the PPT-A gene (Zimmer et al, 1998) and with our conclusion (Cao et al, 1998) that, although SP and NKA are important contributors to the behavioral response to noxious thermal stimuli, they are not required for intensity encoding. Presumably other neurotransmitters, likely glutamate and/or CGRP (calcitonin gene-related peptide), sufficiently activate dorsal horn neurons so as to maintain normal behavioral thresholds.…”
Section: Thermal Deficits In the Mutant Micesupporting
confidence: 82%
See 1 more Smart Citation
“…These data are also consistent with previous reports of behavioral deficits in animals lacking the PPT-A gene (Zimmer et al, 1998) and with our conclusion (Cao et al, 1998) that, although SP and NKA are important contributors to the behavioral response to noxious thermal stimuli, they are not required for intensity encoding. Presumably other neurotransmitters, likely glutamate and/or CGRP (calcitonin gene-related peptide), sufficiently activate dorsal horn neurons so as to maintain normal behavioral thresholds.…”
Section: Thermal Deficits In the Mutant Micesupporting
confidence: 82%
“…Furthermore, selective NK-1 receptor antagonists are antinociceptive in animals (Hill, 2000). There is, however, less agreement among studies of mice with a deletion of the PPT-A gene (Cao et al, 1998;Zimmer et al, 1998) or of the NK-1 receptor (De Felipe et al, 1998;Weng et al, 2001). Some studies reported a significant loss of injury-induced enhancement of nociceptive processing (central sensitization), but others only found deficits in acute pain processing (Cao et al, 1998;De Felipe et al, 1998;Mansikka et al, 1999;Mansikka et al, 2000;Martinez-Caro and Laird, 2000;Laird et al, 2001;Weng et al, 2001).…”
Section: Introductionmentioning
confidence: 90%
“…4 A-E), consistent with the distribution pattern of endogenous DORs. The Myc-DOR1 was further found to be localized on the cell surface but absent in CGRP-ir vesicles in small DRG neurons cultured from PPT-A gene-deleted (Tac1 −/− ) mice (37) (Fig. 4 A-D).…”
Section: Resultsmentioning
confidence: 99%
“…[89][90][91] The current study also showcases the power of applying comparative genomics, using the genomes of species as highly diverged as humans and birds, to gain insights into the regulatory mechanisms supporting the expression of genes relevant to mental health. This approach will greatly accelerate our identification and characterisation of the regulatory systems and networks required to drive the proper expression of neuronally expressed genes critical to human psychiatric health and will allow an understanding of how deficiencies within these systems might promote the initiation and progression of psychiatric disease.…”
Section: Discussionmentioning
confidence: 99%